Current status of transcriptional regulation systems - May, Tobias (Springer Netherlands, 2006)
Many attempts have been undertaken to control transgene activity in mammalian cells. This is of importance for both applied biotechnology and basic research activities. State of the art regulatory systems use elements for transgene regulation which are unrelated to host regulatory networks and thus do not interfere with endogenous activities. Most of these regulation systems consist of transregulators and transregulator responding promoter elements that are derived from non mammalian origin. Apart from the tetracycline (Tet) regulated system which is most widely used for conditional gene expression at the moment, a number of new systems were created. These systems have been significantly refined and their performance makes them suitable for regulating transgenes not only in cellular systems but also in transgenic animals and for human therapeutic use.